The gamma ray detection threshold temperature of different superheated droplet detectors. (September 2018) - Sarkar, Rupa; Mondal, Prasanna Kumar; Chatterjee, Barun Kumar
Abstract: The response of superheated droplet detectors (SDD) loaded with four different active liquids, R-12 (CCl2 F2 ), R-114 (C2 Cl2 F4 ), R-134a (C2 H2 F4 ) and R-610 (C4 F10 ) have been studied to obtain the gamma ray detection threshold temperature ( T γ ) of the respective detectors. A 137 Cs gamma ray source is used for this study. To obtain T γ from the experimental data a phenomenological model has been used. Result indicates that T γ maintains a linear relationship with the limit of superheat ( T lim ) of different active liquids used in SDD. It indicates that the limit of superheat of a liquid can be used for the prediction of its gamma ray detection threshold temperature. Highlights: 137 Cs gamma ray source is used for studying the gamma detection threshold temperature ( T γ ) of superheated droplet detectors. To obtain T γ accurately a phenomenological model is used for fitting the experimental data. T γ varies linearly with the limit of superheat of active liquids which can be used for the prediction of T γ of any liquid.